Comparative gene expression analysis of Fas and related genes in preeclamptic and healthy women: A cross-sectional study - Zaima Ali; Saba Khaliq; Ph.D; Saima Zaki; Hafiz Usman Ahmad; Khalid Pervaiz Lone (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Preeclampsia is a hypertensive disorder of pregnancy affecting about 2-10% pregnancies worldwide. mRNA expression of tumor necrosis factor alpha (TNF- α ), Fas, and FasL have been reported to be altered in placental bed in preeclamptic pregnancies. We hypothesized that the expression of these genes is also altered in peripheral blood mononuclear cells (PBMCs) in preeclampsia. Objective: To compare the expression of Fas receptor and related genes in PBMCs of preeclamptic and normotensive pregnant women. Materials and Methods: A cross-sectional comparative study comprising of 18 cases and 18 controls was designed. 5 ml of venous blood was drawn and collected considering aseptic measures. Buffy coat was separated by centrifugation and stored at -20°C. Favor Prep total RNA Isolation Kit (Favorgen, Taiwan) was used for RNA extraction. The mRNA expression of TNF- α , Fas, and FasL was measured by real-time polymerase chain reaction in PBMCs in preeclamptic and normal pregnancies. Results: A significant increase in mRNA expression of TNF- α , Fas, and FasL (p ≤ 0.001) was observed in PBMCs of preeclamptic pregnancies compared to the control group (p ≤ 0.001). Moreover, a significant positive correlation was found between the TNF- α mRNA expression and Fas and FasL (p ≤ 0.001). Conclusion: The results lead to the conclusion that mRNA expression of TNF- α , Fas, and FasL in the maternal PBMCs is altered in preeclamptic pregnancies and might contribute to the pathogenesis of the disease.